Effect of drip irrigation and organic mulches on growth, yield and water-use efficiency of French bean (Phaseolus vulgaris) - CHAUHAN, SHRADHA; AGRAWAL, GHANSHYAM; KUMAR, PARDEEP; CHAUHAN, ANJALI; THAKUR, KULDEEP; SINGH, UPENDER (The Indian Journal of Agricultural Sciences, 2023)
French bean (Phaseolus vulgaris L.) is an important crop for green and dry beans while tender pods as vegetable. An experiment was conducted during March–June 2021 at the research farm of Dr Y S Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh to assess the effect of different irrigation levels and organic mulches on soil properties, growth and productivity of French bean. Experiment was laid out in Randomized Block Design with 3 replications comprising of 7 treatments. The study resulted, that plant height, no. of pods per plant, days to first harvest and yield of French bean were significantly affected by different irrigation levels and organic mulches. The maximum yield, water use efficiency, B:C ratio were observed under treatment I1M2 (80% ETc + Grass mulch). Therefore, adopting drip irrigation with mulching can contribute to increasing irrigated area and enhancing yield potential of French bean in the mid hill zone of Himachal Pradesh.